Clinical and microbiological characteristics of Flavobacterium indologenes infections associated with indwelling devices. - Hsueh, P R (1996)
Clinical infections caused by Flavobacterium indologenes have never been documented. Thirteen isolates derived from seven patients with indwelling device-associated F. indologenes infections were identified from 1 April through 30 November 1995. The antimicrobial susceptibilities to 20 antimicrobial agents of the isolates, the cellular fatty acid chromatograms for the isolates, and the random amplified polymorphic DNA (RAPD) patterns generated by arbitrarily primed PCR of the isolates were studied. The antibiotypes and RAPD patterns differed among the isolates recovered from different patients. However, both antibiotypes and RAPD patterns were identical among the five isolates from one patient with multiple episodes of central venous catheter-associated bacteremia within a 1.5-month period and between the two isolates from another patient suffering from two episodes of catheter-related bacteriuria at an interval of 14 days. It is documented that the recurrent infections in each of these two patients were caused by a single F. indologenes clone, respectively. Identical antibiotypes and RAPD patterns were also demonstrated between two isolates from a patient with ventilator-associated pneumonia, one recovered from an endotracheal aspirate and the other derived from a blood specimen 10 days later, indicating the invasive nature of F. indologenes. Two cellular fatty acid chromatograms were identified among these isolates. All of the isolates showed in vitro resistance to cephalothin, cefotaxime, ceftriaxone, moxalactam, aztreonam, aminoglycosides, erythromycin, clindamycin, vancomycin, and teicoplanin. F. indologenes should be included as an etiologic agent of infections associated with the use of indwelling devices.